(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Leishmania disease is a disease caused by several types of protozoan parasites inside the cell belonging to the genus Leishmania, which are transmitted to humans through the bite of a female sand fly.It is considered an endemic disease in Syria and causes an important health problem due to the defective scars it leaves in the absence of treatment. This study was conducted to compare the efficacy of treating cutaneous leishmaniasis with intralesional injection of 12% aqua sodium chloride solution with intralesional injection of sodium meglumine solution. The study included 63 patients, whose ages ranged from one year to seventy-one years. The number of males was 40 patients and the number of females was 23 patients. We found that treatment with sodium meglumine solution gave an excellent response of 70.9% after 6 weeks, while treatment with hypertonic sodium chloride solution 12% led to an excellent response of 50% after 6 weeks. Pain was the most common side effect and was more severe when treatment with hypertonic sodium chloride solution 12%. Our study showed that hypertonic sodium chloride solution 12% is a safe treatment with no systemic side effects, and it can be considered an inexpensive alternative to sodium meglumine solution by intralesional injection.